Benefits and drawbacks of computer-based assessment and feedback systems: Student and educator perspectives - Debuse, Justin C. W.; Lawley, Meredith (British journal of educational technology, 2016)
Providing students with high quality feedback is important and can be achieved using computer‐based systems. While student and educator perspectives of such systems have been investigated, a comprehensive multidisciplinary study has not yet been undertaken. This study examines student and educator perspectives of a computer‐based assessment and feedback system at undergraduate and postgraduate levels across a range of disciplines, course sizes and educator experience levels. The results suggest that students and educators may enjoy quality, efficiency and quantity benefits from such an approach, without the drawbacks of low personalisation and specificity identified within the literature. Time and effort are, however, required by educators for training and installation. Thus, workload and training allowances are recommended for practitioners, particularly for large courses where group assignments require highly personalised feedback.